Negative pole piece as well as preparation method and application thereof
By controlling the D01 particle size of graphite particles and adding specific binders to the negative electrode slurry, the problem of sticking rollers in the preparation of negative electrode sheets of lithium-ion batteries is solved, and the bonding force and cycle stability of the electrode are improved.
Patent Information
- Application Number
- CN202510057318.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
AI Technical Summary
During the preparation of the negative electrode sheet of lithium-ion batteries, sticky rollers are prone to occur, which affects the production efficiency and the surface quality of the electrode.
By controlling the D01 particle size range of graphite particles to be 2.5-4.0 μm, and adding polyacrylonitrile aqueous binder and vinyl carbonate to the negative electrode slurry, the viscosity and the adhesion are improved to reduce the roll pressure sticking phenomenon.
It effectively reduces the phenomenon of roll pressure sticking, improves the adhesion and flexibility of the negative electrode sheet, and improves the stability of the lithium battery cycle.
Smart Images

Figure BDA0005241803990000041 
Figure BDA0005241803990000051 
Figure BDA0005241803990000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a negative electrode sheet and a preparation method and application thereof. Background Art
[0002] Compared with lead-acid batteries, nickel-cadmium batteries and nickel-metal hydride batteries, lithium-ion batteries have the advantages of high energy density, high power density, high operating voltage, good cycle performance, long life, low self-discharge and wide temperature adaptability. Lithium-ion batteries usually include positive electrode sheets, negative electrode sheets, separators and electrolytes. The positive electrode sheets and negative electrode sheets have an important influence on the electrical properties of lithium-ion batteries.
[0003] The positive electrode sheet and the negative electrode sheet include positive or negative active materials, conductive agents, binders and current collectors. There are three main types of widely used lithium-ion battery binders: polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR) emulsion and carboxymethyl cellulose (CMC). In addition, water-based binders with polyacrylic acid (PAA), polyacrylonitrile and polyacrylate as main components also occupy a certain market. PVDF is the first widely used lithium-ion battery electrode binder with strong electrochemical corrosion resistance and can be applied to positive electrode materials. However, PVDF requires N-methylpyrrolidone (NMP) as a solvent, and the cost of recovering the solvent is high, which will cause certain pollution to the environment. Therefore, water-based binders and CMC binders are usually used in negative electrodes such as graphite with relatively low potential.
[0004] In the negative electrode slurry system, the surface of graphite particles is hydrophobic. CMC molecules have both hydrophobic parts (main chains without carboxyl modification) and hydrophilic parts (carboxyl modification). Therefore, CMC is adsorbed on the surface of graphite particles through the hydrophobic main chains without carboxyl modification. On the other hand, the hydrophilic carboxyl groups can make the graphite adsorbed with CMC suspended in water. The two characteristics of CMC are combined to disperse graphite in water.
[0005] After the negative electrode sheet is dried, rolling is used to improve the compaction density and uniformity of the negative electrode active material in the current collector, and to improve the adhesion between the active material and the current collector. During the high-temperature baking process of the negative electrode sheet, the volatilization of pure water causes certain pores and surface tension differences to form from the surface to the inner layer of the electrode sheet. The capillary action and surface tension difference generated by the pores induce the binder to float to the surface of the electrode sheet and enrich. The binder enriched on the surface causes the negative electrode sheet to stick to the roller when it is rolled. When preparing the negative electrode sheet, if the "sticky roller" phenomenon occurs (that is, the negative electrode sheet adheres to the roller during the rolling process after drying), this will not only affect the production efficiency, but may also cause problems such as uneven electrode thickness and poor surface quality. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a negative electrode sheet with improved roller-bonding; another object of the present invention is to provide a negative electrode sheet.
[0007] The present invention discloses a method for preparing a negative electrode sheet, comprising the following steps:
[0008] S1: Mix CMC (sodium carboxymethyl cellulose) and water to form a uniform CMC glue solution;
[0009] S2: Evenly mix a portion of the CMC slurry prepared in S1 with polyacrylonitrile and a conductive agent; evenly mix with graphite and the remaining CMC slurry; knead and then add water to adjust the viscosity of the negative electrode slurry to 8000-12000 mPa·s; the D01 of the graphite particles is 2.5-4.0 μm;
[0010] S3: demagnetizing, filtering, degassing, and coating the negative electrode slurry on the surface of the current collector; drying, rolling, slitting, and die-cutting to obtain negative electrode sheets.
[0011] In order to suppress the floating of the electrode sheet binder and improve the bonding strength of the negative electrode sheet, the industry focuses on studying the working mechanism of the binder, the selection of the binder, the proportion of the binder in the formula, the coating and baking process, etc. There are few studies on the physical and chemical properties of the negative electrode graphite active material, especially the compatibility of the graphite D01 particle size selection with the binder. Controlling the D01 range of graphite particles can effectively reduce the roller sticking phenomenon and improve the bonding strength of the negative electrode.
[0012] Polyacrylonitrile water-based binder has good anti-oxidation and anti-reduction capabilities, and has less swelling. The combination of polyacrylonitrile and CMC promotes the uniform dispersion of graphite in the binder, improves the brittleness of CMC, and can effectively improve the flexibility of the pole piece and improve the cycle stability of lithium batteries.
[0013] The D01 of the graphite particles is 2.5-4.0 μm, which means that 1% of the total number of graphite particles has a particle size within the range of 2.5-4.0 μm.
[0014] Furthermore, in step S1, the solid content of the CMC glue is 1.0-2.0%; and the viscosity is 1000-10000 mPa.s.
[0015] Furthermore, in step S2, the mass of the graphite: the mass of the conductive agent: the mass of the CMC: the mass of the polyacrylonitrile is (95.0-97.0):(0.5-2.0):(0.1-0.5):(2.0-3.0); and the solid content of the material after uniform kneading is 60-65%.
[0016] Furthermore, in the step S2, ethylene carbonate (EC) is added before kneading; the ratio of the mass of the added ethylene carbonate to the total mass of the solids in the positive electrode slurry is 0.4-1.4%.
[0017] The particle size distribution of negative electrode graphite active material D01 has a significant positive correlation with the bonding strength of negative electrode plates. The reduction of fine particles in the negative electrode graphite main material inhibits the floating of the plate binder during coating and baking. The addition of EC balances the surface tension difference between the surface and inner layers of the plate after the volatilization of pure water. Combined with the selection of D01 particle size, it effectively improves the poor floating of the binder during coating and baking, and improves the roller-pressing and sticking phenomenon of the negative electrode plate.
[0018] Furthermore, in step S2, the D01 of the graphite is 3.0-4.0 μm; and the ratio of the mass of the added ethylene carbonate to the total mass of the solid in the positive electrode slurry is 0.8-1.0%.
[0019] Adding ethylene carbonate to the negative electrode slurry can not only reduce the sticking phenomenon but also improve the bonding strength of the negative electrode plate. However, if the amount added is too high, the discharge capacity of the assembled lithium-ion battery will be reduced. When the amount of ethylene carbonate added is controlled within the range of 0.8-1.0%, the discharge capacity of the assembled lithium-ion battery will not be significantly reduced.
[0020] Furthermore, in step S3, the coating speed is 40-60 m / min, the coating temperature is 80-120°C, the blowing frequency is 15-30 Hz, and the exhaust frequency is 15-30 Hz; the double-layer coating surface density is 85-95 g / m 2 .
[0021] Furthermore, in step S4, the rolling pressure is 50-100t, the rolling speed is 60-80m / min, the front stretching tension is 120-180N, and the rear stretching tension is 180-240N.
[0022] Rolling increases the compaction density and uniformity of the negative electrode active material in the current collector, and increases the adhesion between the active material and the current collector.
[0023] Furthermore, in step S1, the conductive agent includes one or more of carbon black, conductive graphite, nano-carbon fiber, and carbon nanotube.
[0024] The present invention also discloses a negative electrode sheet, which is prepared by the preparation method as described above and has a bonding force of 0.150-1.505 N / mm.
[0025] The present invention also discloses an application of a negative electrode plate, such as the negative electrode plate described above is applied to the production of lithium-ion batteries.
[0026] The invention discloses a method for preparing a negative electrode sheet, wherein the negative electrode active material graphite is screened after graphitization, a D01 screening index is increased, and the D01 of the graphite is controlled within a range of 2.5-4.0 μm, which can effectively reduce the phenomenon of roller sticking. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0028] The particle size distribution of graphite particles was measured by BT-9300ST laser particle size analyzer.
[0029] EC (ethylene carbonate) is a solid crystal at room temperature. It needs to be heated in a water bath before use at 60°C for more than 2 hours and then added after it melts.
[0030] The negative electrode current collector is copper foil.
[0031] Example 1
[0032] Preparation of negative electrode sheet:
[0033] S1: Add pure water and CMC into the double planetary mixer in sequence to form a CMC glue solution that is evenly dissolved and dispersed. The solid content of CMC glue is 1.5% and the viscosity is 8000mPa.s.
[0034] S2: Add polyacrylonitrile, 60wt% CMC glue, and conductive agent (carbon black) in a double planetary mixer to form a conductive glue premix that is dissolved and dispersed evenly, then add negative electrode active material graphite (where the D01 of graphite particles is 2.55μm) and 40wt% CMC glue, and use the low-speed twist paddle and high-speed dispersion disk of the mixer to shear and knead to ensure that the components are mixed and dispersed evenly, and the kneading solid content is 62.0%. Finally, add pure water to adjust the viscosity to 10786mPa·s. The mass of the conductive agent: the mass of CMC: the mass of polyacrylonitrile is 96:1.5:0.3:2.2.
[0035] S3: After demagnetization and filtration, the finished negative electrode slurry is transported into the transfer tank, vacuumed, and the air pressure is controlled to ≤-0.085Mpa for degassing, and temporarily stored under slow stirring. The coating machine is a reciprocating double-layer coating machine, the coating oven length is 40m, the coating speed is 50m / min, the coating temperature is 80-120℃, the blowing frequency is 15-30Hz, and the exhaust frequency is 15-30Hz. The specific parameter settings are shown in Table 1. Coating surface density 90g / m 2 , rolling, pressing pressure 80t, rolling speed 70m / min, front stretching tension 150N, rear stretching tension 200N, slitting, die cutting, to obtain the negative electrode sheet.
[0036] Table 1 Oven setting parameters of negative electrode during drying process
[0037]
[0038] Example 2
[0039] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 2.61 μm.
[0040] Example 3
[0041] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 2.90 μm.
[0042] Example 4
[0043] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 3.26 μm.
[0044] Example 5
[0045] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 3.34 μm.
[0046] Example 6
[0047] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 3.38 μm.
[0048] Example 7
[0049] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 3.72 μm.
[0050] Example 8
[0051] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 3.83 μm.
[0052] Example 9
[0053] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 3.91 μm.
[0054] Example 10
[0055] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 3.91 μm; at the same time, ethylene carbonate (EC) is added before kneading, and the ratio of the mass of ethylene carbonate added to the total mass of solids in the positive electrode slurry is 0.4%.
[0056] Embodiment 11
[0057] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 3.91 μm; at the same time, ethylene carbonate (EC) is added before kneading, and the ratio of the mass of ethylene carbonate added to the total mass of solids in the positive electrode slurry is 0.6%.
[0058] Example 12
[0059] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 3.91 μm; at the same time, ethylene carbonate (EC) is added before kneading, and the ratio of the mass of ethylene carbonate added to the total mass of solids in the positive electrode slurry is 0.8%.
[0060] Embodiment 13
[0061] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 3.91 μm; at the same time, ethylene carbonate (EC) is added before kneading, and the ratio of the mass of ethylene carbonate added to the total mass of solids in the positive electrode slurry is 1.0%.
[0062] Embodiment 14
[0063] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 3.91 μm; at the same time, ethylene carbonate (EC) is added before kneading, and the ratio of the mass of ethylene carbonate added to the total mass of solids in the positive electrode slurry is 1.2%.
[0064] Embodiment 15
[0065] The difference from Example 1 is that the added negative electrode active material graphite particles have a D01 of 3.91 μm; at the same time, ethylene carbonate (EC) is added before kneading, and the ratio of the mass of ethylene carbonate added to the total mass of solids in the positive electrode slurry is 1.4%.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 2.38 μm.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 2.41 μm.
[0070] Comparative Example 3
[0071] The difference from Example 1 is that the added graphite particles of negative electrode active material have a D01 of 2.45 μm.
[0072] Table 2 Viscosity test results
[0073]
[0074]
[0075] As shown in Table 2, the D01 particle size screening of graphite has no obvious effect on the viscosity of the negative electrode slurry, and the addition of EC has no obvious effect on the viscosity of the negative electrode slurry.
[0076] Performance Test:
[0077] 1. Measurement of the adhesion of coated electrodes: The electrode sampling specification is 25mm wide * 130mm long, and the tensile force is tested by a tensile testing machine.
[0078] Test method: Use 25mm wide 3M double-sided tape, stick the 3M double-sided tape on the stainless steel plate, stick the sample electrode on the 3M double-sided tape, use a 2Kg roller to roll back and forth 3 times, then fix the stainless steel plate on the base of the tensile machine, fix the end of the electrode on the tensile machine fixture, and use a tensile speed of 300mm / min to test the electrode bonding data. The test results are shown in Table 3.
[0079] 2. Roller sticking defect rate: 10,000m of negative electrode sheets are produced and cut into negative electrode sheets. The appearance of the negative electrode sheets is poor due to roller sticking. The appearance of the obtained negative electrode sheets is observed, and the number of negative electrode sheets with poor appearance due to roller sticking accounts for the percentage of the total number of negative electrode sheets.
[0080] 3. Capacity test of discharge capacity: the negative electrode plates obtained in Examples 10 to 14 were assembled into lithium-ion batteries, wherein the positive electrode active material was lithium iron phosphate, the positive electrode current collector was aluminum foil, the separator was (12+4) μm, PP film and ceramic coated on one side, and the electrolyte was a commercial product. Specific operation: constant current charging to 3.65V, constant current discharge to 2V, and finally back to 30% SOC, and the capacity temperature was 28-33°C.
[0081] Table 3 Adhesion and roller sticking defect rate test results
[0082]
[0083]
[0084] As shown in Table 3, the classification test of D01 screening of negative electrode active material graphite particles was verified, and it was found that the particle size distribution of the main graphite material D01 has an obvious positive correlation with the bonding strength of the negative electrode sheet. The reduction of fine graphite particles can inhibit the floating of the electrode sheet binder during coating and baking, which can not only effectively improve the bonding strength of the negative electrode sheet, but also effectively improve the rolling sticking phenomenon. At the same time, the addition of EC balances the surface tension difference between the surface and inner layer of the electrode sheet after the volatilization of pure water, and combined with the D01 particle size selection, it effectively improves the poor floating of the binder during coating and baking, and further improves the rolling sticking phenomenon of the electrode sheet.
[0085] Table 4. Test results of discharge capacity at different capacities
[0086] Case Discharge capacityAh Example 10 136.8 Embodiment 11 136.7 Example 12 136.0 Embodiment 13 135.7 Embodiment 14 135.9 Implementation Case 15 132.2 Implementation Case 16 129.5
[0087] According to Table 4, when the EC addition amount is less than or equal to 1%, the differential discharge capacity has no obvious effect. When the EC addition amount is greater than 1%, the differential discharge capacity loss is greater than 2.5%.
[0088] Therefore, as shown in Table 3 and Table 4, it is optimal to control the D01 of graphite particles in the negative electrode slurry to 3.5-4.0μm and match the 1% EC addition. And according to this solution, normal production continued for 3 months, and the electrode sheet rolling sticking rate was stable at 0.5%-1% without rebound.
[0089] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a negative electrode sheet, characterized in that: The following steps are involved: S1: Mix CMC and water to form a uniform CMC glue solution; S2: Evenly mix a portion of the CMC slurry prepared in S1 with polyacrylonitrile and a conductive agent; evenly mix with graphite and the remaining CMC slurry; knead and then add water to adjust the viscosity of the negative electrode slurry to 8000-12000 mPa·s; the D01 of the graphite particles is 2.5-4.0 μm; S3: demagnetizing, filtering, degassing the negative electrode slurry, and coating it on the surface of the current collector; drying, rolling, slitting, and die-cutting to obtain negative electrode sheets.
2. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In the step S1, the solid content of the CMC glue is 1.0-2.0% and the viscosity is 1000-10000 mPa.s.
3. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In the step S2, the mass of the graphite: the mass of the conductive agent: the mass of the CMC: the mass of the polyacrylonitrile is 95.0-97.0: 0.5-2.0: 0.1-0.5: 2.0-3.0; and the solid content of the material after uniform kneading is 60-65%.
4. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In the step S2, ethylene carbonate is added before kneading; the ratio of the mass of the added ethylene carbonate to the total mass of the solids in the positive electrode slurry is 0.4-1.4%.
5. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In the step S2, the D01 of the graphite is 3.0-4.0 μm; and the ratio of the mass of the added ethylene carbonate to the total mass of the solid in the positive electrode slurry is 0.8-1.0%.
6. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In step S3, the coating speed is 40-60 m / min, the coating temperature is 80-120°C, the blowing frequency is 15-30 Hz, and the exhaust frequency is 15-30 Hz; the double-layer coating surface density is 85-95 g / m 2 .
7. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In the step S4, the rolling pressure is 50-100t, the rolling speed is 60-80m / min, the front stretching tension is 120-180N, and the rear stretching tension is 180-240N.
8. The method for preparing a negative electrode sheet according to claim 1, characterized in that: In the step S1, the conductive agent includes one or more of carbon black, conductive graphite, nano-carbon fiber, and carbon nanotube.
9. A negative electrode plate, characterized in that: The composite material is prepared by the preparation method as described in any one of claims 1 to 8, and has a bonding force of 0.150-1.505 N / mm.
10. An application of a negative electrode sheet, characterized in that: The negative electrode plate as claimed in claim 9 is used in the production of lithium-ion batteries.